Cardiovascular risk and inflammation in a population with autoimmune diseases: a narrative review - Bertoni, Camilla; Mazzocchi, Alessandra; Leone, Ludovica; Agostoni, Carlo; Filocamo, Giovanni (Frontiers in Immunology, 2024)
Juvenile Systemic Connective Tissue Diseases (JSCTD) are a heterogeneous group of chronic autoimmune diseases, associated with dyslipidemia and increased cardiovascular risk are related. Studies from the last 10 years, from 2013 to 2022, on lipid profiles in JSCTD were collected. Different studies on lipid profiles in children affected by JSCTD were selected, because the aim is to analyze the cardiovascular risk and the possibility of atherosclerosis in these patients in whom, sometimes, corticosteroid therapies and immunosuppressants increase the state of dyslipidemia. Several studies have shown that autoimmune diseases with an inflammatory substrate also share abnormalities in lipid profile and increased cardiovascular risk. Specifically, associations have been found between Juvenile Systemic Connective Tissue Diseases and elevated triglycerides, TC-C (Total Cholesterol), LDL-C (Low-Density Lipoprotein), low HDL-C (High-Density Lipoprotein), and increased risk of developing diseases such as myocardial infarction, peripheral vascular disease, pulmonary and arterial hypertension, and atrial fibrillation. Supplementation with alpha-linolenic acid (ALA) on the other hand has also been analyzed with positive results in reducing inflammatory parameters, such as IL-6 (Interleukin-6), CRP (C-reactive protein), and fasting glucose, in subjects with dyslipidemia. These observations suggest that supplementation with ALA, an omega-3 precursor, may positively modulate both the inflammatory status and dyslipidemic conditions in patients with autoimmune disorders.